Metodología de cría de Doru lineare (Dermaptera: Forficulidae) en laboratorio, con notas sobre su comportamiento - Romero Sueldo, Gladys Mabel (2008)
“Laboratory breeding method for Doru lineare (Dermaptera: Forficulidae) with reference to its behavior”. A detailed description of a novel method for the breeding of Doru lineare is presented. The earwigs were bred using plastic cages and corrugated paperboard. Eighty-five percent of the eggs were deposited into plastic cups containing a wet cotton wick. Each egg mass contained a mean of 26,9 eggs, 95% of them emerging. Maternal care of the offspring took 6 to 8 days, ending when the nymphs reached the second instar. The female’s behavior is essential to enhance egg viability preventing fungal infections. Under our breeding conditions, the nymphal stage duration lasted an average of 26,4 ± 2,4 days.